1984
DOI: 10.1212/wnl.34.5.658
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphate polyneuropathy

Abstract: Organophosphorus-induced delayed polyneuropathy (OPIDP) is initiated by the phosphorylation of a protein neurotoxic esterase (NTE) in the nervous system. A second step, the "aging" of the phosphoryl-enzyme complex, is required to produce the toxic effect. The experimental evidence for this molecular target and the importance of the aging process are reviewed. The catalytic activity of NTE has been used to develop an in vitro screening test that may distinguish the organophosphorus compounds (OPs) that cause ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
1
5

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(50 citation statements)
references
References 0 publications
0
44
1
5
Order By: Relevance
“…Out of fifty patients 26% of the patients had mild depression of serum pseudocholinesterase levels and 42% of patients had moderate depression of serum cholinesterase levels and 32% of patients showed severe depressions of cholinesterase levels. 11,12 Mortality rates of 26% were observed in our study, 6% of the patients required ventilatory support and two patients (4%) developed Intermediate syndrome. Respiratory paralysis was the major cause of death.…”
Section: Discussionmentioning
confidence: 47%
“…Out of fifty patients 26% of the patients had mild depression of serum pseudocholinesterase levels and 42% of patients had moderate depression of serum cholinesterase levels and 32% of patients showed severe depressions of cholinesterase levels. 11,12 Mortality rates of 26% were observed in our study, 6% of the patients required ventilatory support and two patients (4%) developed Intermediate syndrome. Respiratory paralysis was the major cause of death.…”
Section: Discussionmentioning
confidence: 47%
“…Besides these manifestations of acute onset, some organophosphates may produce delayed neurotoxic ef fects on both the peripheral and central nervous system, even in the absence of acute cholinergic symptoms [7,8]. Indeed, experimental studies have shown that exposure to chemicals like desbromoleptophos might occur with out acute symptoms because the mean lethal dose is 50 times the neurotoxic dose [9].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature a few cases of organophosphate-induced delayed polyneuropa thy (OPIDP) are reported, appearing after a variable period ranging from 1 to 5 weeks following initial expo sure [10][11][12][13]. One case has been reported as GuillainBarrd syndrome [12], The delay between exposure and onset of these late complications depends in part on the dose and the nature of the involved chemical [8,13]. The clinical picture of OPIDP is characterized by a distal, symmetric, and predominantly motor polyneuropathy with wasting and flaccid weakness mainly in legs and feet [8,11].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an organophosphate-induced delayed polyneuropathy (OPIDP) may result from a distal dying back axonopathy [110], believed to be caused by phosphorylation of the enzyme neuropathy target esterase (NTE) [111]. OPIDP appears 1 to 3 weeks after exposure with cramping pain in the legs, paresthesias, and motor weakness.…”
Section: Nerve Agentsmentioning
confidence: 99%